(untitled) (Rudarsko-geološko-naftni zbornik, 2023)
Massive tailings have resulted from the extensive use of placer deposits in Central Kalimantan, Indonesia, by artisanal and small-scale gold mining (ASGM) activities. Recently, the placer deposits and their tailings have been exploited for heavy minerals. In this study, geochemical and magnetic analyses were carried out on these deposits to identify the prospect of REE (rare earth element) exploration in the materials already collected by ASGM activities. Samples were collected from ten different locations. For each location, two different fractions were prepared for analyses, i.e. the heavy mineral (HM) fraction and the panned (M60) fraction. All HM and M60 samples were subjected to magnetic susceptibility measurements, but only representative samples were subjected to x-ray fluorescence (XRF) measurements (for Si, Ti, Fe, Zr, and Al) and to inductively coupled plasma-emission spectroscopy (ICP-OES) measurements (for Eu, Tb, Dy, and Sc). The results showed that the concentrations of major elements (Ti, Fe, Zr, and Al) vary significantly from deposits along one river to another, while the concentration of Si is rather similar. Compared to M60 samples, the HM samples have higher concentrations of Ti, Fe, Zr, Al, and Sc, implying that the sluice-box separation enhances the concentration of valuable minerals. Magnetic susceptibility is found to be correlated with Fe and Sc concentrations, confirming the potential use of magnetic measurements as a complementary tool for Fe and Sc exploitation in placer deposits. It is believed that both the source rocks and the sedimentary settings of these deposits determine whether certain elements (Sc, Fe, and Zr) are present or absent in Central Kalimantan placer deposits. The prospect of exploring and exploiting Sc in these placer deposits might augment the ASGM activities in Central Kalimantan.